Lysosomal cholesterol accumulation in macrophages leading to coronary atherosclerosis in CD38−/− mice. Issue 6 (28th January 2016) - Xu, Xiaoyang; Yuan, Xinxu; Li, Ningjun; Dewey, William L.; Li, Pin‐Lan; Zhang, Fan
Abstract: The disruption in transportation of oxLDL‐derived cholesterol and the subsequent lipid accumulation in macrophages are the hallmark events in atherogenesis. Our recent studies demonstrated that lysosomal Ca 2+ messenger of nicotinic acid adenine dinucleotide phosphate (NAADP), an enzymatic product of CD38 ADP‐ribosylcyclase (CD38), promoted lipid endocytic trafficking in human fibroblast cells. The current studies are designed to examine the functional role of CD38/NAADP pathway in the regulation of lysosomal cholesterol efflux in atherosclerosis. Oil red O staining showed that oxLDL concentration‐dependently increased lipid buildup in bone marrow‐derived macrophages from both wild type and CD38 −/−, but to a significant higher extent with CD38 gene deletion. Bodipy 493/503 fluorescence staining found that the deposited lipid in macrophages was mainly enclosed in lysosomal organelles and largely enhanced with the blockade of CD38/NAADP pathway. Filipin staining and direct measurement of lysosome fraction further revealed that the free cholesterol constituted a major portion of the total cholesterol segregated in lysosomes. Moreover, in situ assay disclosed that both lysosomal lumen acidity and the acid lipase activity were reduced upon cholesterol buildup in lysosomes. In CD38 −/− mice, treatment with Western diet (12 weeks) produced atherosclerotic damage in coronary artery with striking lysosomal cholesterol sequestration in macrophages. These data provide the first experimental evidence that the proper function of CD38/NAADP pathway plays an essential role in promoting free cholesterol efflux from lysosomes and that a defection of this signalling leads to lysosomal cholesterol accumulation in macrophages and results in coronary atherosclerosis in CD38 −/− mice.